Vision of Nuclear Power Deployment in Latin America and the Caribbean: A Focus on Small Modular Reactors and the Regional Experience of Central Argentina de Elementos Modulares - Alejandra Loreto Alfaro; Florencia Rentería; Camila Araujo (International Journal of Nuclear Security, 2025)
Increasing the number of nuclear power reactors in the Latin American and Caribbean region presents technical, financial, regulatory, and environmental challenges. Focused on fostering economic stability, growth, and human capacity development, the deployment of small modular reactors (SMRs) emerges as a key aspect in the region’s energy landscape. The emergence of SMRs represents an opportunity for multidisciplinary cooperation among different sectors. To comprehensively address the challenges related to the protection of nuclear facilities in the region, the Tlatelolco Treaty and the Non-Proliferation Treaty should be strengthened as legally binding instruments to enforce the safety and safeguarding principles integral to the peaceful applications of nuclear energy. Financial, technical, human resource, and digital challenges must also be addressed to enable opportunities for integrating nuclear technology into the region’s power grids. This article serves as a call of action to collaborate on harnessing the power of nuclear energy while championing gender diversity and international cooperation for the benefit of the region’s socioeconomic landscape. Drawing from the exemplary Central Argentina de Elementos Modulares (CAREM) project in Argentina, which showcases the integration of SMRs into the national energy mix, this paper underscores the multiple aspects that the SMR market needs to address for deployment in the region. This study provides an overview of the region's energy and nuclear landscape, highlighting challenges and opportunities in various sectors. It provides introductory elements for planning a strategy for the use of nuclear power in the region, emphasizing joint cooperation among Latin American and Caribbean countries to pave the way for a sustainable and prosperous future driven by a clean, safe and reliable energy solution. In particular, CAREM-25 is a 25 MWe prototype SMR based on pressurized water reactor technology and was designed and launched by the National Atomic Energy Commission of Argentina (CNEA). The project is under construction and has an estimated criticality date of late 2027. The Argentine case also provides outstanding examples of women in leadership positions, such as General Manager of the CAREM project Dr. Sol Pedre and former President of the CNEA Dr. Adriana Serquis.
Keywords: Small Modular Reactors; Latin America and the Caribbean; CAREM